Wujud Kebudayaan Masyarakat Adat Cikondang dalam Melestarikan Lingkungan - Deni Miharja (UIN Sunan Gunung Djati Bandung, 2016)
This study departs from human life lived long enough in a community, where the community will create a rule or a handle on life that can be used as a way of survival for the creation of a safe, serene and peaceful. The rule could be religious and also can be a culture. Indigenous peoples with all its potential able to be creative to build an environment that is completely self-contained and is also able to preserve the nature of the damage. As a result of the natural environment inhabited by indigenous communities today rescued from various natural disasters. This phenomenon, would be an interesting study material for study. The Society has a certain cultural values that differ from one another. The indigenous peoples are a society that is in life comes with a quirk inherited his ancestors, either in the form of a view of life, religious traditions and values of other cultures that sought to be maintained and implemented in his life as a commandment of life for the benefit of their ancestors The Cikondang society known as the Sunda ethnic and categorized as indigenous communities, because until now still cling to the traditions of his ancestors. It stands out that of the indigenous peoples Cikondang Cikondang is the persistence of indigenous peoples to preserve and utilize the environment to life. This can be seen, when the rainy season Cikondang region is not exposed to landslides, even a water source can be fully utilized for agriculture, so that agricultural produce in abundance. Likewise third dry season Cikondang indigenous peoples do not worry about lack of water even position in the hills of the mountains.